Bird Diversity and its Potential for Tourism Activities In Mandeh Mangrove Forest, West Sumatra, Indonesia - Novita, Aulya; Mukhta, Erizal; Novarino, Wilson (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Avitourism is a form of tourism that focuses on bird watching intheir natural habitat. The existence of mangrove forests is very important in anarea because it is a habitat for various types of wildlife, especially birds. Thisstudy aims to analyze bird diversity and its potential in tourism activities in theMandeh mangrove ecosystem area. This research was conducted fromFebruary to April 2024. The method used was the point count method. Datacollection of bird species and numbers was carried out at 15 observation points.The distance of each observation point is 150 meters with an observation radiusof 50 meters. Data collection was carried out for 10 minutes at each point.Observations were conducted for four days, and continued with bird speciesidentification. Data analysis used was Shannon Wiener diversity index,evenness index and richness index. The results found 32 bird species from 18families. Dominated by the Apodidae and Estrildidae families. The diversityindex value is 2.17 with moderate index criteria. evenness index 0.63 which isincluded in the uneven category and a wealth index of 4.96 with a high wealthcategory. Birds that have ecotourism attractions found are 1 type of endemicbird, not found raptor birds, 2 types of birds listed on the IUCN, 7 types ofmelodious sound birds and 16 types of beautiful feathers, so that the Mandehmangrove ecosystem area has potential.